2019
DOI: 10.1021/acsenergylett.9b00738
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Sites between Cobalt Nitride and Cobalt Act as Bifunctional Catalysts for Hydrogen Electrochemistry

Abstract: Hydrogen (H 2 ) electrochemistry primarily consists of two reactions: hydrogen evolution reaction in water for H 2 production (HER) and hydrogen oxidation reaction in hydrogen fuel cells for H 2 utilization (HOR). The realization of future hydrogen economy necessitates the development of low-cost and competent electrocatalysts for both HER and HOR. Herein, we report that partial nitridation of cobalt nanoparticles on current collectors results in rich Co 2 N/Co interfacial sites, which exhibit bifunctional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 45 publications
2
102
0
Order By: Relevance
“…The model showed the electron density of Cu in Cu/Cu 2 O NWAs minus the electron density of Cu in pure Cu NWAs, and the extra electronic cloud was the yellow part. Thus, it can be deduced that high electronic density of Cu induced the decrease of reaction barrier and suppresses the competitive H 2 production, leading to high conversion rate, Faradaic efficiency, and selectivity of Cu/Cu 2 O for NRA.…”
Section: Figurementioning
confidence: 99%
“…The model showed the electron density of Cu in Cu/Cu 2 O NWAs minus the electron density of Cu in pure Cu NWAs, and the extra electronic cloud was the yellow part. Thus, it can be deduced that high electronic density of Cu induced the decrease of reaction barrier and suppresses the competitive H 2 production, leading to high conversion rate, Faradaic efficiency, and selectivity of Cu/Cu 2 O for NRA.…”
Section: Figurementioning
confidence: 99%
“…Importantly, these two peaks are positively shifted to higher binding energies in PW-Co 3 N NWA/ NF. Specifically, the deconvoluted peaks at 778.6 and 793.9 eV can be assigned to metallic Co states in Co 3 N 30,31 while the peaks at 786.9 and 803.7 eV can be attributed to satellite peaks 29,32 . Two more peaks located at 782.4 and 799.2 eV could be originated from the surface oxidation, which has also been broadly observed 33,34 .…”
Section: Synthesis and Characterization Of Pw-co 3 N Nanowire Arraysmentioning
confidence: 99%
“…Moreover, Markovic and co-workers [21] demonstrated that optimizing adsorption of hydroxyl species (OH ad ) can promote hydrogen oxidation rate in alkaline media. Inspired by this, a series of electrocatalysts with bi-active sites consisting of metals and metal oxides/hydroxide have been reported, in which the metal acts as the hydrogen adsorption site and the other component promotes OH ad adsorption [22][23][24][25]. Ni/NiO/C with enhanced HOR performance in alkaline medium was synthesized by Sun's group [26].…”
Section: Introductionmentioning
confidence: 99%